answer me as fast as possible
Attachments:
![](https://hi-static.z-dn.net/files/d79/a9874801bb4a194fdccdbdfd4e638c10.jpg)
smartyprince:
hi
Answers
Answered by
1
please refer to the attachment
Hope it will help you
Hope it will help you
Attachments:
![](https://hi-static.z-dn.net/files/dd1/7d5d2ed8bbebe17eca556b98ada1923a.jpg)
![](https://hi-static.z-dn.net/files/db4/891b0a458a5e944d5dc283b7f78dcb61.jpg)
Answered by
3
(1) X - 3 /6 - 1 = 6X+1/3
X-3 - 6 = 6(6X+1)/3
X - 9 = 12X + 2
12X - X = -11
11X = -11
X = -1
(2) X - 1 /3 - 1/12 = 4X+1/4
=> 4 ( X - 1 ) - 1 = 12 ( 4X + 1 )/4
=> 4X - 4 - 1 = 12X + 3
=> 12X - 4X = -5-3
=> 8X = -8
=> X = -8/8 = -1
(3) X + 3/4 = 2X-3/5
=> 5 ( X + 3 ) = 4 ( 2X - 3 )
=> 5X + 15 = 8X - 12
=> 8X - 5X = 15+12
=> 3X = 27
=> X = 27/3 = 9
( 4 ) X + 1 /3 = X - 2/ 4 + 1/3
=> X + 1 / 3 = 3 ( X - 2 ) + 4/12
=> 12 ( X + 1 ) = 3 ( 3X - 2)
=> 12X + 12 = 9X - 6
=> 12X - 9X = -6-12
=> 3X = -18
=> X = -18/3 = -6
★ HOPE IT WILL HELP YOU ★
X-3 - 6 = 6(6X+1)/3
X - 9 = 12X + 2
12X - X = -11
11X = -11
X = -1
(2) X - 1 /3 - 1/12 = 4X+1/4
=> 4 ( X - 1 ) - 1 = 12 ( 4X + 1 )/4
=> 4X - 4 - 1 = 12X + 3
=> 12X - 4X = -5-3
=> 8X = -8
=> X = -8/8 = -1
(3) X + 3/4 = 2X-3/5
=> 5 ( X + 3 ) = 4 ( 2X - 3 )
=> 5X + 15 = 8X - 12
=> 8X - 5X = 15+12
=> 3X = 27
=> X = 27/3 = 9
( 4 ) X + 1 /3 = X - 2/ 4 + 1/3
=> X + 1 / 3 = 3 ( X - 2 ) + 4/12
=> 12 ( X + 1 ) = 3 ( 3X - 2)
=> 12X + 12 = 9X - 6
=> 12X - 9X = -6-12
=> 3X = -18
=> X = -18/3 = -6
★ HOPE IT WILL HELP YOU ★
Similar questions
Science,
8 months ago
English,
8 months ago
English,
8 months ago
Social Sciences,
1 year ago
Biology,
1 year ago